Rogue protocol eaudiobook - Wells, Martha (The Murderbot Diaries, 2018)
The third thrilling book in the increasingly popular Murderbot Diaries, which began with All Systems Red. SciFi's favorite antisocial A.I. is back on a mission. The case against the too-big-to-fail GrayCris Corporation is floundering, and more importantly, authorities are beginning to ask more questions about where Dr. Mensah's SecUnit is. And Murderbot would rather those questions went away. For good. Martha Wells' Rogue Protocol is the third in the Murderbot Diaries series, starring a human-like android who keeps getting sucked back into adventure after adventure, though it just wants to be left alone, away from humanity and small talk. Read Rogue Protocol and find out why Hugo Award winner Ann Leckie wrote "I love Murderbot!"